2017
DOI: 10.21577/0103-5053.20170033
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Inhibition of Mycobacterium tuberculosis Enoyl-acyl Carrier Protein Reductase and Antimycobacterial Activity of Novel Pentacyanoferrate(II)-isonicotinoylhydrazones

Abstract: Tuberculosis remains among the top causes of death triggered by a single pathogen. Herein, a greener synthetic approach for isonicotinoylhydrazones is described using ultrasound energy. These compounds were used as starting materials for synthesizing pentacyanoferrate(II)-isonicotinoylhydrazones, which inhibited the reaction catalyzed by Mycobacterium tuberculosis 2-trans-enoyl-ACP(CoA) reductase (MtInhA) in a time-dependent manner. The most active coordination complex showed an increase of more than ten-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…On the other hand, these compounds showed significant structural differences that could aid their interaction with InhA enzyme. Interestingly, we found that some of these complexes were better in vitro inhibitors of InhA than IQG-607 with inhibition rate values 10-fold larger, though with similar MIC values (Gazzi et al, 2017 ).…”
Section: Developing New Pharmacological Strategies Using Metalsmentioning
confidence: 68%
See 1 more Smart Citation
“…On the other hand, these compounds showed significant structural differences that could aid their interaction with InhA enzyme. Interestingly, we found that some of these complexes were better in vitro inhibitors of InhA than IQG-607 with inhibition rate values 10-fold larger, though with similar MIC values (Gazzi et al, 2017 ).…”
Section: Developing New Pharmacological Strategies Using Metalsmentioning
confidence: 68%
“…A series of cyanoferrate(II) complexes containing isonicotinoylhydrazone ligands (Figure 4 ) was prepared and measurements of InhA enzyme inhibition and antitubercular activity against a drug-susceptible M. tuberculosis strain were carried out (Gazzi et al, 2017 ). There was a modest difference in electrochemical potential among all of those complexes, ranging from 337 to 426 mV vs. Ag|AgCl, which is expected as they are bound through an analogous pyridinic nitrogen.…”
Section: Developing New Pharmacological Strategies Using Metalsmentioning
confidence: 99%
“…This gene encodes an NADH-reductase involved in the production of mycolic acid in the Mycobacterial wall [73]. Although these are the gene mutations most associated with H resistance, mutations in other genes, such as kasA, ahpC, and drfA, were also discovered [21,[74][75][76].…”
Section: Discussionmentioning
confidence: 99%